Optimalisasi Manajemen Persediaan melalui Implementasi Kartu Stok pada Minuman Racikan di P4S X Kulon Progo - Arini Dara Pitasari; Siwitri Munambar; Geraldo Adinugra Rimartin (Lembaga Yasin AlSys, 2025)
Biofarmaka processing MSMEs (UMKM) such as P4S X in Kulon Progo play a strategic role in supporting the agriculture and health sectors based on natural ingredients, yet face challenges in inventory management due to the absence of a structured and documented recording system. This condition hinders accurate monitoring of raw material availability and poses risks to production continuity. This study aims to design and implement a stock card system as a simple, effective, and operationally appropriate inventory recording solution for MSMEs. A qualitative descriptive method with a case study approach was employed, with data collected through direct observation, semi-structured interviews, and documentation of inventory management activities at P4S X. The results show that the stock card system improves recording accuracy, facilitates regular inventory monitoring, and supports the determination of reorder points. Furthermore, its implementation fosters more disciplined recording habits among warehouse managers. The study concludes that the stock card system is a relevant, applicable inventory management tool with a positive impact on the operational efficiency of biofarmaka-processing MSMEs. The findings imply that simple yet targeted managerial interventions can significantly strengthen supply chains and support the sustainability of MSME production.